2023
DOI: 10.1002/ohn.501
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events Associated With Tracheostomy: A MAUDE Database Analysis

Vishal Narwani,
Sydney Dacey,
Michael Z. Lerner

Abstract: ObjectiveTracheotomy is one of the most common procedures. Although tracheostomy complications have been extensively studied, literature related to device complications is scarce. The objective of this study is to describe complications associated with tracheostomies utilizing the Manufacturer and User Facility Device Experience (MAUDE) database.Study DesignRetrospective cross‐sectional study.SettingThe US Food and Drug Administration's (FDA) MAUDE database (2015‐2020).MethodsThe FDA's MAUDE database was queri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In our study, we demonstrated that although the risk of puncture during PDT in certain areas may appear to be low, all the regions studied carry a risk of vascular puncture. Bleeding during or immediately after PDT is rare, though not exceptional, thatand accounts for 10% of all PDT-associated complications [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we demonstrated that although the risk of puncture during PDT in certain areas may appear to be low, all the regions studied carry a risk of vascular puncture. Bleeding during or immediately after PDT is rare, though not exceptional, thatand accounts for 10% of all PDT-associated complications [ 7 ].…”
Section: Discussionmentioning
confidence: 99%